A picture is worth a thousand words: A content analysis of Facebook profile photographs - Hum, Noelle J.; Chamberlin, Perrin E.; Hambright, Brittany L.; Portwood, Anne C.; Schat, Amanda C.; Bevan, Jennifer L. (Computers in human behavior, 2011)
► College students’ Facebook profile photographs are examined and compared by gender. ► Content analysis was used to code the 150 profile pictures for six categories. ► Profile photographs tend to be posed, inactive, appropriate, and contain only the subject. ► Profile picture albums typically contained more than 20 pictures. ► None of the profile picture categories significantly differed by gender. This research examines identity construction and gender roles in social networking sites by studying and comparing the profile photographs of male and female Facebook users. Specifically, the number of photos in the profile album and the content of the main profile picture are studied by coding specific pictures, and determining if the content and amount of profile pictures differ significantly by gender. Participants include male and female Facebook users between the ages of 18 and 23 who are currently enrolled in a college or university. Profile pictures tended to be inactive, posed, appropriate, and only including the subject. The content and amount of Facebook profile photographs also did not significantly vary by gender. Implications of these findings, as well as suggestions for future research, are discussed.